Probability of a false-negative HIV antibody test result during the window period: a tool for pre- and post-test counselling. (March 2015) - Taylor, Darlene; Durigon, Monica; Davis, Heather; Archibald, Chris; Konrad, Bernhard; Coombs, Daniel; Gilbert, Mark; Cook, Darrel; Krajden, Mel; Wong, Tom; Ogilvie, Gina
Failure to understand the risk of false-negative HIV test results during the window period results in anxiety. Patients typically want accurate test results as soon as possible while clinicians prefer to wait until the probability of a false-negative is virtually nil. This review summarizes the median window periods for third-generation antibody and fourth-generation HIV tests and provides the probability of a false-negative result for various days post-exposure. Data were extracted from published seroconversion panels. A 10-day eclipse period was used to estimate days from infection to first detection of HIV RNA. Median (interquartile range) days to seroconversion were calculated and probabilities of a false-negative result at various time periods post-exposure are reported. The median (interquartile range) window period for third-generation tests was 22 days (19–25) and 18 days (16–24) for fourth-generation tests. The probability of a false-negative result is 0.01 at 80 days' post-exposure for third-generation tests and at 42 days for fourth-generation tests. The table of probabilities of falsely-negative HIV test results may be useful during pre- and post-test HIV counselling to inform co-decision making regarding the ideal time to test for HIV.